EFFECT OF METAPHORICAL THINKING LEARNING ON IMPROVING ABILITY OF MATHEMATICAL UNDERSTANDING VIEWED FROM INTEREST LEVEL OF STUDENT LEARNING - Nurkolis Nurkolis; Jejen Abdul Fatah; Hoer Mutaqin; Asep Ikin Sugandi; Wahyudin Wahyudin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study aims to obtain a picture of improving the ability of mathematical understanding on the implementation of learning with metaphorical thinking approach in terms of student interest level. The method used in this research is an experiment with factorial design 3 x 2. The population is all high school students in Cianjur Regency with the sample subject is two classes of X in one of senior high school in Cianjur environment. The first class gets learning with metaphorical thinking approach, and the second class gets instruction with direct instruction model. From the research, it can be concluded that there is no difference in the improvement of mathematical understanding among high school students who get the learning with Metaphorical Thinking and Direct Instruction approach. There is a difference in the increase of mathematical understanding among the students whose interest level is high with a medium, low, and low with high, there is no interaction between the learning model and the level of student's learning interest in improving the ability of mathematical understanding.